Using Health Information Resources for People With Cognitive Impairment (digiDEM Bayern): Registry-Based Cohort Study - Weidinger, Florian; Dietzel, Nikolas; Grässel, Elmar; Prokosch, Hans-Ulrich; Kolominsky-Rabas, Peter (JMIR Formative Research, 2025)
Background: Dementia is a growing global health challenge with significant economic and social implications. Underdiagnosis of dementia is prevalent due to a lack of knowledge and understanding among the general population. Enhancing dementia literacy through improved health information–seeking behavior is crucial for the self-determined management of the disease by those affected. Understanding the relationship between dementia literacy, health information–seeking behavior, and the use of various information sources among individuals with cognitive impairment is of high importance in this context. Objective: The aim of this study was to analyze the relevance of different sources of health information from the perspective of people with cognitive impairment, while also evaluating differences based on age, gender, and disease progression. Methods: This study is part of the ongoing project “Digital Dementia Registry Bavaria – digiDEM Bayern.” The Digital Dementia Registry Bavaria is a multicenter, prospective, longitudinal register study in Bavaria, Germany. People with cognitive impairment rated several information sources by using Likert scales with the values unimportant (1) to very important (5). Data were analyzed descriptively, and multiple 2-sample, 2-tailed t tests were used to evaluate differences by cognitive status and gender and using multiple one-way ANOVA to evaluate differences by age group. Results: Data of 924 people with cognitive impairment (531 with dementia, 393 with mild cognitive impairment) were evaluated. The most relevant health information sources were “Personal visit to a medical professional” (mean 3.9, SD 1.1) and “Family / Friends” (mean 3.9, SD 1.2). “Internet” was 1 of the 2 lowest-rated information sources by people with cognitive impairment (mean 1.6, SD 1.1), with nearly three-quarters (684/924, 74%) of the participants rating the source as unimportant. The age-specific analyses showed significant differences for the sources “Internet” (F2,921=61.23; P<.001), “Courses / Lectures” (F2,921=18.88; P<.001), and “Family / Friends” (F2,921=6.27; P=.002) for the 3 defined age groups. There were several significant differences between people with mild cognitive impairment and dementia whereby the first group evaluated most sources higher, such as “Internet” (mean difference=0.6; t640=7.52; P<.001). The only sources rated higher by the dementia group were “TV / Radio” and “Family / Friends,” with none of them showing significant differences. Gender-specific analyses showed women with cognitive impairment valuing every evaluated source higher than men apart from “Internet” (mean difference=0.4; t685=4.97; P<.001). Conclusions: To enhance health and dementia literacy, the best way to communicate health information to people with cognitive impairment is through interpersonal contact with medical professionals and their friends and family. Slight changes in valuation should be considered as the medical condition progresses, along with variations by age and gender. In particular, the evaluation and use of the internet are dependent on these factors. Further research is needed to capture potential changes in the valuation of the internet as a health information source.
CRIS-Team Scopus Importer:2025-01-31
Keywords: cognitive impairment; dementia; digiDEM; Digital Dementia Registry Bavaria; health information; health information–seeking behavior; information sources; mild cognitive impairment